2007
DOI: 10.4049/jimmunol.178.7.4584
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Release from the Basophils of Control and Asthmatic Subjects and a Comparison of Gene Expression between “Releaser” and “Nonreleaser” Basophils

Abstract: Most human blood basophils respond to FcεRI cross-linking by releasing histamine and other inflammatory mediators. Basophils that do not degranulate after anti-IgE challenge, known as “nonreleaser” basophils, characteristically have no or barely detectable levels of the Syk tyrosine kinase. The true incidence of the nonreleaser phenotype, its relationship (if any) to allergic asthma, and its molecular mechanism are not well understood. In this study, we report statistical analyses of degranulation assays perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 30 publications
(53 reference statements)
4
59
1
Order By: Relevance
“…Although it is formally possible that the different yields of basophils from Percoll could result from a difference in density between the basophils of asthmatics and controls, basophils were not detectable in other gradient fractions. The increased numbers of basophils in blood from asthmatics complement a previous analysis of the larger data set showing that maximum percentage histamine released from asthmatics is also higher than control [11]. …”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Although it is formally possible that the different yields of basophils from Percoll could result from a difference in density between the basophils of asthmatics and controls, basophils were not detectable in other gradient fractions. The increased numbers of basophils in blood from asthmatics complement a previous analysis of the larger data set showing that maximum percentage histamine released from asthmatics is also higher than control [11]. …”
Section: Resultssupporting
confidence: 62%
“…We reported previously that basophils from asthmatics show a higher maximum percentage histamine than control basophils [11] and demonstrate here that more basophils are recovered after Percoll centrifugation from the blood of asthmatics than controls. Both characteristics may contribute to the onset or progression of disease.…”
Section: Discussionmentioning
confidence: 75%
“…This reduction in receptor levels occurs because IgE binding is required to stabilize FcεRI at the basophil membrane [14]. Signaling though the FcεRI causes the synthesis and release of substantial amounts of the Th2 cytokines IL-4 and IL-13 that are critical for initiating and maintaining allergic responses [15,16,17,18,19,20,21,22]. FcεRI signaling also stimulated the production of chemokines, particularly IL-8, that stimulate inflammatory cell chemotaxis [22].…”
Section: Introductionmentioning
confidence: 99%
“…MIP-1α chemoattracts B cells, eosinophils and basophils, degranulates eosinophils and induces histamine release from basophils and mast cells whereas MIP-1β does not [22, 23]. MIP-1α and MIP-1β are expressed and produced in various cells and airways associated with asthma [6,7,8,9,10]. Therefore, it is believed that MIP-1α and MIP-1β modify the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that MIP-1α and MIP-1β modify the pathogenesis of asthma [6,7,8,9,10]. A previous paper revealed that MIP-1α production was stimulated by LTD 4 and lipopolysaccharides in alveolar macrophages of rats [11].…”
Section: Introductionmentioning
confidence: 99%